IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DI PERGURUAN TINGGI - Waluyo Erry Wahyudi; H. Jumeri; Sujarot; Ni Putu Wulantari; Singgih Prastawa; Joni Wilson Sitopu (EDU RESEARCH, 2024)
Character education is one of the strategic issues in education in Indonesia today. As an effort to strengthen the character of students, universities need to integrate local wisdom values in the learning process. This study aims to analyse the implementation of local wisdom-based character education in higher education. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations and document reviews. The results showed that the college has integrated local wisdom values such as gotong royong, tolerance, and religiosity in the curriculum, student activities, and campus culture. However, the implementation is still not optimal due to obstacles in socialisation, institutional support, and lecturers' understanding. For this reason, comprehensive efforts are needed from universities to strengthen character education based on local wisdom through policy development, capacity building of lecturers, and collaboration with stakeholders. It is expected that the output of this research can be a reference for universities in developing character education models that are in accordance with the local cultural context.